Application of LoRa with MEH in Maintenance-Free IoT - Minagawa, T.; Kameshima, T.; Mitsuhasi, H.; Hirane, H.; Abdullah, N. (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2025)
With the recent demand for IoT, there has been a growing focus on power supply using energy harvesting technology. Magnetic Energy Harvesting (MEH) has several advantages over other energy harvesting methods, such as solar, thermal, and vibrational energy. However, conventional methods often depend on unstable environmental conditions such as sunlight or temperature differences, which limit continuous operation in indoor or shaded environments. Long Range (LoRa) is a low-power wide-area network (LPWAN) technology designed specifically for IoT devices. By combining LoRa and MEH has the potential to create truly maintenance-free IoT systems that can operate autonomously for long periods of time. The objective of this study is to evaluate whether a LoRa module can be operated using only power harvested from environmental magnetic fields. Experiments were conducted by generating an environmental magnetic field and connecting the MEH coil output to the LoRa communication module through a rectifier and DC-DC converter to verify communication feasibility. As a result, communication was not possible, even using an improved version of LoRa with lower power consumption. The results of this study clarify future considerations for intercommunication. In conclusion, insufficient power supply from the MEH module was identified as the main limitation, and improvements to the power conducting module, LoRa circuit board, DIP switch, and film capacitor will be required to realize maintenance-free IoT systems.